FUSIC HD. Comprehensive haemodynamic assessment with ultrasound. (August 2022) - Miller, Ashley; Peck, Marcus; Clark, Tom; Conway, Hannah; Olusanya, Segun; Fletcher, Nick; Coleman, Nick; Parulekar, Prashant; Aron, Jonathan; Kirk-Bayley, Justin; Wilkinson, Jonathan Nicholas; Wong, Adrian; et al.
FUSIC haemodynamics (HD) – the latest Focused Ultrasound in Intensive Care (FUSIC) module created by the Intensive Care Society (ICS) – describes a complete haemodynamic assessment with ultrasound based on ten key clinical questions: 1. Is stroke volume abnormal? 2. Is stroke volume responsive to fluid, vasopressors or inotropes? 3. Is the aorta abnormal? 4. Is the aortic valve, mitral valve or tricuspid valve severely abnormal? 5. Is there systolic anterior motion of the mitral valve? 6. Is there a regional wall motion abnormality? 7. Are there features of raised left atrial pressure? 8. Are there features of right ventricular impairment or raised pulmonary artery pressure? 9. Are there features of tamponade? 10. Is there venous congestion? FUSIC HD is the first system of its kind to interrogate major cardiac, arterial and venous structures to direct time-critical interventions in acutely unwell patients. This article explains the rationale for this accreditation, outlines the training pathway and summarises the ten clinical questions. Further details are included in an online supplementary appendix.